INDONESIAN ELEMENTARY SCHOOLS TEACHERS™ ATTITUDE TOWARDS VIDEO CONFERENCING PLATFORM IMPLEMENTATION DURING COVID-19 PANDEMIC - Machmud, Muhammad Takwin; Ramadhani, Noer Risky; Sipahutar, Rini Juliani; Manjani, Nurhudayah; Silalahi, Natalia; Damayanti, Nina Afria; Syahrial, Syahrial; Bangun, Melly Br (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2022)
This study is identifying elementary schools teacher attitudes towards video conferencing platform implementation during Covid-19 pandemic. The research aims include (1) to identify teachers™ attitude towards implementing video conferencing platforms for learning (2) to identify teachers' challenges encountered during implementing video conferencing and how to overcome that challenge. The 103 elementary schools teachers were included. The teacher selected by simple random sampling techniques. The questionnaire's content is based on teachers' attitudes toward using video conferencing in the classroom during the COVID-19 epidemic, as measured by the following indicators: efficiency, effectiveness, motivation, and variety of obstacles. The elementary schools teachers™ attitude shows positive responses to video conferencing in learning such as providing various learning activities, providing flexibility in teaching process, easiness to access learning materials, and ease in assessing and monitoring students' learning progress. Furthermore, the result reveals the majority of the elementary schools teachers faced technical issues and availability as obstacles in implementing a video conferencing platform. The majority of elementary schools teachers were able to resolve these technological difficulties by exploring other teaching strategies and seeking professional advice.